Exploring Themes in English Language Teaching Publications in Iran’s Medical Education: A Content Analysis - Samaneh Karami; Afsaneh Dehnad; Iman Alizadeh (Acta Medica Iranica)
The present study explored the trajectories of themes in the English for Medical Purposes (EMP) studies in the Iranian medical education context. Informed with the frameworks of language planning, it juxtaposed the extracted themes with the pillars of English for Specific Purposes (ESP)-needs analysis, learning objectives, materials and methods, and evaluation. It explored the EMP themes in a corpus of 41 documents extracted from Google Scholar, Scopus, ISI, and PubMed databases. Then, the researchers performed a content analysis of the corpus based on a matrix incorporating the title, abstract, introduction, discussion, keywords, and the field of expertise of the author(s) of the documents. The analysis revealed the themes of learners’ need analysis, language skills, learning strategies, cognitive and affective variables, teaching methodology, teaching materials, material evaluation, use of technology, evaluation of learners and learning, program evaluation, and evaluation of instructors. The juxtaposition of the themes with the mainstream pillars showed that although there was a match between the themes and the pillars, the size of the themes falling under each pillar differed. While utilizing technology and affective variables were the most frequent themes, learning materials, language skills, and learner variables were the least frequent ones. Most of the themes matched with the learning objectives pillar; the needs analysis pillar, on the other hand, had the fewest number of themes. Notable gaps, particularly in the areas of instructors' needs, administrative needs, learner variables, and instructor variables were discovered. The study also showed that EMP research predominantly focuses on English for medical academic purposes (EMAP) in the absence of studies on English for Medical Occupational Purposes (EMOP). The findings have implications for EMP research, policy setting, teacher education, and materials development, providing guidance for future research endeavors and contributing to the enhancement of English language education in the field of medical sciences.